Challenges of Implementing PSAK 72 in the Era of Technology Disruption and the COVID-19 Pandemic on Telecommunication Company Revenues - Tasya Anindya Pramesti; Elvia Rosantina Shauki (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Technological disruption coupled with the COVID-19 pandemic has become both a strength and a weakness for companies with the telecommunications industry being an important industry. However, the increase in internet usage, increase in loyalty and decrease in customer dissatisfaction felt by PT Telkom Indonesia are not in line with the decrease in revenue from contracts with customers based on PSAK 72. Using triangulation research methods through interviews and questionnaires with content and thematic analysis techniques, interviews conducted with The company's PSAK PIC results that the decrease in revenue based on PSAK 72 is due to a decrease in the enterprise business line due to the impact of COVID-19, according to Rahayu's research (2020) that the implementation of PSAK 72 has no significant effect on telecommunications companies. The results of the interview resulted that the application of PSAK 72 required synergistic corporate governance to face various challenges. In addition, the increase in loyalty and decrease in customer dissatisfaction is in line with the results of the questionnaire where respondents are satisfied with the innovation and improvement of internet services compared to before the pandemic, meaning that the company is always innovating to maintain customer loyalty.